A two-stage parametric stochastic frontier analysis (SFA) of the efficiency performance of Shari'ah compliant banks: a global evidence. (2018) - Abu-Alkheil, Ahmad; Khartabiel, Ghadeer; Dali, Nuradli Ridzwan Shah Mohd
This paper examines the efficiency performance of 32 Islamic banks (IBs') from Asia, the Middle East, Gulf region, and Europe using the stochastic frontier analysis (SFA). Furthermore, the study utilises the ordinary least squares (OLS) approach to analyse the cause–effect relationship between bank-specific factors and banks' efficiency scores over the period from 2004 to 2014. Findings show that the majority of IBs' appear to be inefficient in terms of both generating profits and controlling costs. Banks' substantial inefficiencies are largely technical and partly scale in nature. Results suggest also that IBs' that are more technically efficient are most likely larger in size with low market-share, highly profitable, well-capitalised, supply more lending, and are less leveraged. Overall, the empirical findings reveal that not all IBs' were equally affected during the period of the global financial crisis of 2007. However, tiny observed variations are mainly due to the country-specific factors.